Pentacene to octacene: the limit of fourfold TIPS-ethynylation - Zeitter, Nico; Hippchen, Nikolai; Baur, Philipp; Unterreiner, Tamara; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F. (Organic materials, 2024)
Soluble acenes beyond hexacene are rare. Their sensitivity complicates isolation, purification and application in devices. To increase the stability of acenes, functionalization with trialkylsilylethynyl substituents prevents [4 + 4] dimerization and oxidation. At the same time, such acenes are soluble and processible. Here we present the modular synthesis of fourfold tri-iso-propylsilylethynyl-ethynylated pentacenes to octacenes and investigate their optical and redox properties, frontier orbital positions (CV, density functional theory calculations) as well as their stability in solution (UV/vis, NMR spectroscopy). We also investigated their magnetic properties as a function of acene length. Pentacene, hexacene and heptacene are sufficiently stable to serve as semiconductors in thin-film transistors - the octacene rapidly decays to its butterfly dimer evidence by time-dependent NMR spectroscopy and crystal structure analysis.
Gesehen am 14.03.2024